HEMA and alginate-based chondrogenic semi-interpenetrated hydrogels: Synthesis and biological bharacterization - Torres, María Luz (2020)
Cartilage tissue engineering (CTE) has the general objective of restoring and improving damaged cartilage. A very interesting strategy of CTE is to combine different polymers to obtain a viscoelastic material. In the present study we have evaluated the applicability of Poly(2-hydroxyethyl methacrylate) networks semi-interpenetrated with sodium alginate for CTE. Alginate-containing hydrogels show an increase in scaffold porosity and swelling capacity, when compared with nonporous poly(2-hydroxyethyl methacrylate) scaffolds. Primary chondrocytes from young rats were cultured on the hydrogels, and an increase in chondrocyte proliferation and chondrocytic markers was observed in alginate-containing hydrogels. Chondrocytic phenotype was preserved on hydrogels containing the lowest amount of crosslinker and initiator (SEMI 3 and SEMI 4). In addition, Nitric oxide production by RAW264.7 macrophages grown on hydrogels was tested and none of the hydrogels showed high levels of this inflammatory marker after 2 days. These results indicate that our alginate-containing hydrogels could be useful for CTE.